Bilingualisme Masyarakat Desa Jayamukti Karajan II dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia di SMP - Irma, Ade; Rosalina, Sinta; Triyadi, Slamet (Peneliti.net, 2024)
This research aims to describe the type of bilingualism that occurs in the community of Jayamukti Karajan II Village, Banyusari District, Karawang Regency. The method used in this research is descriptive qualitative method. The subject of this research is the type of bilingualism that occurs in the Jayamukti Karajan II Village area through interview methods such as with family members and the object of this research is language bilingualism that occurs in the Jayamukti Karajan II Village environment. The research results of the people of Jayamukti Karajan II Village are a bilingual society because many people use two or more languages ​​in their daily lives. In Jayamukti Karajan II Village, people generally use Sundanese and Indonesian. But there are also those who master more than two languages, such as Betawi and Javanese.